Programma: 8 september Saxon; 11 september Culture; 12 september Graham Parker & The Episodes; 14 september Charanga Habanera
Programma: 8 september Saxon; 11 september Culture; 12 september Graham Parker & The Episodes; 14 september Charanga Habanera.